Alterations in the gut microbiome and metabolism with doxorubicin-induced heart failure severity - Wang, Qian; Liu, Meihua; Liu, Tianpei; Li, Long; Wang, Chenyang; Wang, Xiaolin; Rong, Shuling; Zhou, Xuedong (Frontiers in Microbiology, 2024)
Objective: This study aimed to explore the changes in gut microbiota and its metabolites in different pathophysiological stages of doxorubicin (DOX)-induced heart failure (DIHF) and the relationship between gut microbiota and metabolites in various degrees of DIHF.Materials and methods: C57BL/ 6J mice were injected intraperitoneally with 5 mg/kg of DOX once a week for five consecutive weeks. At different times after injection, the cardiac function and histopathological analysis was conducted, the serum levels of creatine kinase, CK-MB, lactic dehydrogenase, and cardiac troponin T were determined. 16S rRNA gene sequencing of feces and the nontargeted metabolomics analysis of serum were performed. Multi-omics analyses were used to explore the correlation between gut microbiota and serum metabolites.The results showed that DOX caused left ventricular (LV) dilation and reduced LV contractility. The levels of myocardial enzymes significantly increase in 3 and 5 weeks after DOX injection. DOX-treated mice showed significant differences in the composition and abundance of gut microorganisms, and the levels of serum metabolites at different times of treatment. Multi-omics analyses showed that intestinal bacteria were significantly correlated with the differential metabolites. Some bacteria and metabolites can be used as biomarkers of DIHF (AUC > 0.8). KEGG analyses showed the involvement of different metabolic pathways in various degrees of DIHF from the control mice.: Marked differences were found in the composition and abundance of gut microorganisms, the levels of serum metabolites and metabolic pathways in different degrees of DIHF. The intestinal bacteria were significantly correlated with differential metabolites in different degrees of DIHF. The gut microbiota may serve as new targets for the treatment of DIHF.